P126 Patient experiences of malignant pleural effusion management: a qualitative study. (11th November 2022) - Addala, DN; Sundaralingam, A; Bedawi, EO; Iqbal, B; Denniston, P; Kanellakis, N; Russell, N; Wrightson, JM; Rahman, NM
Abstract : Introduction: The current pathway in suspected malignant pleural effusion (MPE) involves multiple procedures to achieve diagnosis and fluid control, typically involving pleural aspiration (procedure-1), biopsy (procedure-2) and finally definitive effusion control with talc or an indwelling pleural catheter (IPC, procedure-3). The true patient experience of this pathway is poorly characterised. Methods: An initial retrospective analysis of 56 IPC insertions at a UK tertiary centre (2020–2021) using electronic patient records was undertaken to establish the typical duration of the MPE pathway. Semi structured qualitative interviews were undertaken with a purposive sample of 17 patients at IPC insertion between March-December 2021. Results: Quantitative analysis: 56 patient notes were reviewed. Median time to treatable diagnosis was 46 days (IQR:28–54) and median time to definitive pleural fluid control was 70 days (IQR:45–84) Median 100 mm visual analogue dyspnoea score prior to the final definitive fluid control procedure was 51 mm (IQR:40–59 mm) Qualitative analysis: 17 patients (10 male, 7 female) were interviewed. Breathlessness: Breathlessness 'limiting daily activities' was a common complaint throughout the pathway. 65% (11/17) of patients reported duration of breathlessness greater than one month, with 88% (15/17) stating direct impact on essential daily activity. 35% (6/17) reported the duration of breathlessness to be 'unacceptable'. Procedure Burden: 60% (11/17) of patients reported having to make at least one emergency call for urgent fluid drainage or admission, with comments pertaining to 'being too breathless to wait for the next appointment'. 76% (13/17) had undergone 2 or more pleural procedures prior to IPC insertion. Improving Pathways: 70% (12/17) of patients reported that they would have wanted an IPC inserted earlier and would have been keen to explore a new pathway with pleural biopsy and IPC as the first procedure. Concerns with this pathway included 'not enough time to process information' and being 'too soon' to have an indwelling device. Conclusions: The current pathway in MPE is lengthy and involves multiple procedures. Patients report breathlessness and time to diagnosis as key areas of concern. We propose a novel pathway with the first procedure as pleural biopsy and IPC insertion, which appear more aligned to patient needs and expectations.